Quality Assessment of Sandcrete Blocks in Ibadan – A review (2013)
Sandcrete blocks have been widely used for modern building construction in Nigeria; however cases of incessant building collapse are rampant. The usage of substandard sandcrete blocks is a contributing factor. This research was carried out to assess the engineering properties of sandcrete blocks produced in Ibadan and its environs. Two blocks each of size 450 x 225 x 225mm were purchased from selected block industries at eight sampled locations within the study area. Few units of blocks (450 x 225 x 225mm) conforming to the Nigerian Industrial Standard (NIS 87:2007) were also produced to serve as control samples. The 28th day dry compressive strength test result obtained for the sampled blocks ranges between 0.39-2.34N/mm2. For the control block samples, the average 28th day dry compressive strength of the three tested blocks was 3.02N/mm2. Conclusively, it was observed that the sandcrete blocks produced in major parts of Ibadan were of low quality and substandard; while the control samples were of adequate strength.